2002
DOI: 10.1016/s0304-8853(01)01001-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of magnetic and specific heat measurements at low temperatures in Nd0.5Sr0.5MnO3, Nd0.5Ca0.5MnO3

Abstract: The magnetization at low temperatures for Nd 0.5 Sr 0.5 MnO 3 and Nd 0.5 Ca 0.5 MnO 3 samples showed a rapid increase with decreasing temperatures, contrary to a La 0.5 Ca 0.5 MnO 3 sample. Specific heat measurement at low temperatures showed a Schottky-like anomaly for the first two samples. However, there is not a straight forward correlation between the intrinsic magnetic moment of the Nd 3+ ions and the Schottky-like anomaly.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…In a previous report 15 we showed that a two-level-Schottky function ͑only one doublet͒ did not fit properly our experimental data at low temperatures. The same result was verified for all the experimental data presented here.…”
Section: ͑1͒contrasting
confidence: 67%
See 1 more Smart Citation
“…In a previous report 15 we showed that a two-level-Schottky function ͑only one doublet͒ did not fit properly our experimental data at low temperatures. The same result was verified for all the experimental data presented here.…”
Section: ͑1͒contrasting
confidence: 67%
“…We have already reported a short version of preliminary results about these topics. 15 However, as far as we know, detailed specific-heat measurements in these compounds have not been published yet.…”
Section: Introductionmentioning
confidence: 99%
“…All of these compounds presented a Schottky-type anomaly at low temperatures. 15,16 Here, we report a general magnetic characterization and specific heat measurements in the full temperature interval, between 2 and 300 K, for the same five samples.…”
Section: Introductionmentioning
confidence: 99%
“…The entropy of the magnetic transition is 1.27 and 2.46 J/(mol⋅K) for Nd 0.5 Sr 0.5 MnO 3 and Nd 0.55 Sr 0.45 MnO 3 , respectively, which makes 10 and 20% of their theoretical values. This testifies to the magnetically biphase state (see also [7]) of the materials under study. It is interesting to note that Sasaki et al [5] observed a well-defined peak of the thermal capacity in the region of the antiferromagnetic-ferromagnetic transition for the Nd 0.5 Sr 0.5 MnO 3 single-crystal sample.…”
Section: Resultsmentioning
confidence: 59%